Analisis Penerapan SAK EMKM Dalam Menyusun Laporan Keuangan UMKM Di Lingkungan Universitas Persada Indonesia Y.A.I - Adita, Azkiya Shafa; Andhara, Nuurul Shadrina; Maghfira; Sari, Bida (Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the application of Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) among MSMEs within Persada Indonesia Y.A.I University environment. Employing a qualitative approach with in-depth interviews of 7 MSME actors, the research reveals a significant gap between expected accounting standards and actual financial reporting practices. Key findings demonstrate that 100% of respondents have not implemented SAK EMKM, primarily due to limited knowledge, insufficient socialization, and accounting comprehension barriers. The study identifies financial recording as predominantly simple, unstructured, and non-compliant with accounting standards. Critical recommendations include systematic interventions through socialization programs, continuous training, and technical assistance to enhance MSME accounting capacities, ultimately improving financial reporting quality and financing access.